OCCURRENCE OF ABNORMALITY IN THE EYE OF CHANNA PUNCTATUS AND THE TAL DEFORMITY IN HETEROPNEUSTES FOSSILIS FROM IMPHAL (INDIA) - ZENITH, N.G.; GAMBHIR, R.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
The paper deals with the incidence of abnormality observed in a common fresh water fish, Channa punctatus belonging to the family Channidae from a pond in the vicinity of the first author's residence. It also deals with the tail deformity in Heteropneustes fossilis from Loktak lake, Manipur, The comparative morphometric characters between the normal and the abnormal Channa punctatus species is also comparatively studied in the paper.